Cellular mechanisms underlying central sensitization in a mouse model of chronic muscle pain - Yu-Ling Lin; Zhu-Sen Yang; Wai-Yi Wong; Shih-Che Lin; Shuu-Jiun Wang; Shih-Pin Chen; Jen-Kun Cheng; Hui Lu; Cheng-Chang Lien (eLife, 2022)
Chronic pain disorders are often associated with negative emotions, including anxiety and depression. The central nucleus of the amygdala (CeA) has emerged as an integrative hub for nociceptive and affective components during central pain development. Prior adverse injuries are precipitating factors thought to transform nociceptors into a primed state for chronic pain. However, the cellular basis underlying the primed state and the subsequent development of chronic pain remains unknown. Here, we investigated the cellular and synaptic alterations of the CeA in a mouse model of chronic muscle pain. In these mice, local infusion of pregabalin, a clinically approved drug for fibromyalgia and other chronic pain disorders, into the CeA or chemogenetic inactivation of the somatostatin-expressing CeA (CeA-SST) neurons during the priming phase prevented the chronification of pain. Further, electrophysiological recording revealed that the CeA-SST neurons had increased excitatory synaptic drive and enhanced neuronal excitability in the chronic pain states. Finally, either chemogenetic inactivation of the CeA-SST neurons or pharmacological suppression of the nociceptive afferents from the brainstem to the CeA-SST neurons alleviated chronic pain and anxio-depressive symptoms. These data raise the possibility of targeting treatments to CeA-SST neurons to prevent central pain sensitization.